P-367 Centromeric motif AA of the KIR: the best subrogate marker that defines Alloimmune Reproductive Failure. (30th June 2022) - Gil Laborda, R; Carrillo de Albornoz, E; Vidal, J; Verdú, V; De la Fuente, A; Fariñas, M; Garcia Segovia, A; Pintado Vera, D; Vicario, J.L; Ros Berruezo, F; Cañadas, F.M; Ordenes, M; et al.
Abstract: Study question: Should the centromeric and telomeric motifs been studied separately and taked them in to account in women with recurrent reproductive failure? Summary answer: The results show that when the classic KIR study is performed, there is a 12, 5% of AA centromeric KIR patients with reproductive failure unidentified. What is known already: During human pregnancy, the decidua is mainly populated by NK lymphocytes that express immunoglobulin-type receptors (KIR) recognizing their HLA-C ligands from trophoblast. The objective of this study was to analyze the association of KIR-HLAC phenotypes in couples with sterility, recurrent pregnancy loss (RPL), recurrent implantation failure (RIF), and fetal death (FD) in comparison with reference population and fertile control. Study design, size, duration: It is a retrospective real-life observational study from 2015 to 2019 Participants/materials, setting, methods: The frequency of the KIR and HLA-C genes were analyzed in 397 women and their partners with reproductive failure. We compare them with 33 fertile controls and reference Spanish population. KIR and HLA-C genotypes of the patients and controls were determined by Lifecodes Sequence-Specific Oligonucleotides (SSO) Typing KIT (Diagnostica Longwood®) performed at Centro de Transfusiones de la Comunidad de Madrid and those of controls at the Hospital Universitario Clínico San Carlos. Main results and the role of chance: Centromeric (Cen) AA was the most frequent KIR genotype in women with unexplained RPL and RIG with respect to reference Spanish population (p = 0.001 and 0.02, respectively). Moreover, cenAA was associated with 1.51-fold risk of RPL and 1.2-fold risk of RIF. On the other hand, BB KIR showed lower risk of any reproductive failure tan non-BB KIR (0.12; p < 0.001). HLA-C1C1/C1C1 women and partner were significantly lower in RPL-Group (p < 0.001) and RIF-Group (p = 0.04). Indeed, the combination cenAA/C1C1 women with C1C1 partners were significantly higher in the control group compared with RPL (p = 0.009) and RIF (0.04) with 5-fold of successful pregnancy outcome. In our cohort, cenAA KIR was a more accurate biomarker tan classic AA KIR haplotype for RPL- and RIF-associated risk. Limitations, reasons for caution: The fact of having stratified a lot by groups means that a small number of patients is obtained in each subgroup, which makes it more difficult to conclude the results. Wider implications of the findings: Our study demonstrates the importance of the complete KIR genotype study, which would give us more comprehensive information on the behavior of NK cells, moreover we propose that centromeric KIR classification is superior to the KIR classical haplotypes, better identifying those patients with potential KIR-HLA-C mismatch. Trial registration number: Not applicable